The Effect of Using Project Base Learning (PjBL) Models on Students' Creative Thinking Skills in Solar System Materials - Vivit Nurhikmah Havita; Sjaifuddin Sjaifuddin; asep saefullah; Lukman Nulhakim; Diana Ayu Rostikawati (Jurnal Pembelajaran Fisika, 2021)
This study aims to determine the achievement and improvement of the abilities gained by students with project-based learning models (PjBL). The method used in this study is a pre-experimental method with research design one group pretest-posttest. This study uses one class. The population of this study was all students of class VII A with a total of 36 students. The study instrument used was a test of creative thinking skills and non-test abilities consisting of creativity, presentation and percentage, and the implementation of the learning model. The result of this study obtained by paired t-test showed that there is a possibility of using the PjBL model to the creative thinking skills with a significance value of 0.000. These results indicate that PjBL affects creative thinking skills. In addition, the improvement of creativity based on the test of creative thinking skills has a value of 0.56 (56%) with medium category, the average value of innovative products is 85.71% with outstanding classes, and the performance & percentage are 73 with good classes.Keywords: creative thinking skills, project-based learning (PjBL), solar system materialsDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202110